The Determinants of Filariasis Prevention (Elephantiasis Disease) in Lumut Maju Village, Lumut Sub-district, Central Tapanuli Regency - Lasmarida Br Silalahi; Zulfendri; Surya Utama (Britain International of Exact Sciences (BIoEx) Journal, 2020)
This research deals with the determinants of filariasis prevention (elephantiasis disease) in Lumut Maju Village, Lumut Sub-district, Central Tapanuli Regency. This research is a qualitative type of research with domain analysis. The study was conducted in Lumut Maju Village, Lumut Sub-district, Central Tapanuli Regency and work units related to the research problem. The results shows that In the context of filariasis prevention, the local government has not coordinated and established networks with relevant SKPDs and in partnership with relevant NGOs and academics. Handling of patients that aims to prevent and limit disability by providing care training to patients and families has not been done to the maximum. Control of risk factors does not work well because the patient is not maximally netted.